Allergic contact dermatitis to nickel in ophthalmic frames - Robert McQuaid (Journal of Current Science and Technology, 2021)
Contact dermatitis from a xenobiotic irritant or allergen, negatively impacts quality of life. Nickel is the most prevalent contact allergen in studies. In the late 18th and early 19th century nickel allergy was an occupational hazard, while today nickel exposure is predominantly from consumer goods. Nickel allergy is prevalent throughout the world, more frequently in women. Limiting chronic nickel exposure and preventing sensitization is the best treatment. Consumer items such as jewelry, especially earrings and other piercings, metal fasteners on clothing, watches, coin money and cell phones are common sources of exposure. Both the innate and adaptive immune systems have been shown to be involved in the complicated epidermal processing of nickel as an allergen. The optometric patient population frequently wears eyeglass frames contain nickel, raising the risk of nickel exposure, sensitization and contact dermatitis. Optometrists should be aware of nickel allergy from eyeglass frames and recommended treatment options.